Comparison of haemoglobin mass across elite endurance sports and within-subject reliability using the optimised CO re-breathing method - Green, D. J.; Lobb, C.; Scott, B.; Turner, G. (Journal of Science and Medicine in Sport, 2026)
Objectives Total haemoglobin mass (tHbmass) is a critical factor in endurance performance. The aim of this study was to compare tHbmass between elite endurance athletes of different sports and assess the reliability of the optimised carbon monoxide rebreathing (oCOR) method in elite endurance athletes. Design A retrospective analysis was conducted on 99 male and 75 female elite endurance athletes from athleticslong (22 male/22 female), athleticsmiddle (33 male/24 female), swimming (28 male/17 female), and triathlon (16 male/12 female). Results Linear regression modelling revealed tHbmass was positively associated with age, body mass and sex (p<0.001). After adjusting for age, body mass, and sex, athleticslong and triathlon exhibited greater tHbmass than swimming (+9.5%, 3.8-15.4%; +9.1%, 3.8-15.0%) and athleticsmiddle (+6.1%, 2.1-11.9%; +5.7%, 1.4-11.5%) respectively. No difference was observed between athleticslong and triathlon (0.4%, -4.1 - 5.8%) or between athleticsmiddle and swimming (3.1%, -1.3% - 8.8%) (values represent % difference with 95% confidence intervals). Analysis of within-subject reliability for tHbmass measurements showed homoscedastic error and a standard error of measurement of 23±3g, indicating that measurement error represents a larger proportion of smaller tHbmass values than of larger ones. Conclusions These findings demonstrate that elite athletes from distinct endurance disciplines can exhibit sport specific haematological adaptations. In addition, this study provides reliability data that can assist practitioners working in elite sport to identify the minimum detectable difference and inform the optimal number of replicate measurements using the oCOR method.